2019
DOI: 10.1029/2019gl084470
|View full text |Cite
|
Sign up to set email alerts
|

Extended U.S. Tornado Outbreak During Late May 2019: A Forecast of Opportunity

Abstract: The second half of May 2019 was an unusually active period for tornadic thunderstorms across the U.S. Great Plains, Midwest, and lower Great Lakes. While this period typically coincides with the peak climatological frequency of tornadoes, preliminary reports of tornadoes were over triple the expected 30‐year average. Multiple‐day outbreaks of tornadoes are not unprecedented in the United States; however, this event was perhaps the first to be forecast at subseasonal lead times (3–4 weeks) by the Extended Range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…Additionally, tornadoes are more likely to occur in Phases 1–4 of the global wind oscillation (GWO) when atmospheric angular momentum is low (Gensini & Marinaro, 2016; Moore, 2018). Statistical models have been developed based on these climate modes to predict severe storm activity on the S2S time scale (Baggett et al, 2018; Gensini et al, 2019; Lepore et al, 2017). However, the ENSO, MJO, and GWO explain limited variability of tornado activity.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, tornadoes are more likely to occur in Phases 1–4 of the global wind oscillation (GWO) when atmospheric angular momentum is low (Gensini & Marinaro, 2016; Moore, 2018). Statistical models have been developed based on these climate modes to predict severe storm activity on the S2S time scale (Baggett et al, 2018; Gensini et al, 2019; Lepore et al, 2017). However, the ENSO, MJO, and GWO explain limited variability of tornado activity.…”
Section: Introductionmentioning
confidence: 99%
“…This severe weather forecast is based on synoptic-scale atmospheric instability [e.g., convective available potential energy (CAPE) and low-level wind shear (LLWS)] from numerical weather forecast models and observations. To extend the current forecast lead time for tornadogenesis to subseasonal time scales (i.e., 14-30 days of lead time), several studies have explored a potential link between U.S. tornado activity and the Madden-Julian oscillation (MJO; Madden and Julian 1972), which is defined by the convective activity over the Maritime Continent propagating eastward around the equatorial tropics with a 30-90-day period (e.g., Thompson and Roundy 2013; Barrett and Gensini 2013; Barrett and Henley 2015;Gensini and Marinaro 2016;Tippett 2018;Baggett et al 2018;Moore and McGuire 2020;Gensini et al 2019). Thompson and Roundy (2013) found that in March-May, the chances of violent tornado outbreaks in the United States are maximized during MJO phase 2, when the convection over the Indian Ocean is enhanced (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies also explored the impact of interactive relationship between MJO and global wind oscillation (GWO), which is defined by the global atmospheric angular momentum, on the U.S. tornado activity (Gensini et al 2019;Moore and McGuire 2020). Moore and McGuire (2020), for instance, explored the interactive impact of GWO and MJO on U.S. tornado days during different seasons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the occurrence and frequency of tornado and hail activity in the central United States can be skillfully predicted weeks in advance using the MJO (Baggett et al, ). Similarly, a case study of the May 2019 tornado outbreak over the central United States shows that the favorable supercell conditions were probabilistically predicted nearly 4 weeks in advance (Gensini et al, ). Beyond severe weather, the occurrence of increased periods of cloud‐to‐ground lightning strikes was shown to show skill for lead times of up to 15 days (Tippett and Koshak, ).…”
Section: Advances In Understanding S2s Predictability and Skillmentioning
confidence: 99%